Health workforce needs in Malawi: analysis of the Thanzi La Onse integrated epidemiological model of care - She,B; Mangal,TD; Prust,ML; Heung,S; Chalkley,M; Colbourn,T; Collins,JH; Graham,MM; Jewell,B; Joshi,P; Li,Lin I; Mnjowe,E; et al. (Human Resources for Health, 2024)
Background: To make the best use of health resources, it is crucial to understand the healthcare needsof a population – including how needs will evolve and respond to changing epidemiological context and patient behaviour – and how this compares to the capabilities to deliver healthcare with the existing workforce. Existing approaches to planning either rely on using observed healthcare demandfrom a fixed historical period or using models to estimate healthcare needs within a narrow domain(e.g., a specific diease area or health programme). A new data-grounded modelling method is proposed by which healthcare needs and the capabilities of the healthcare workforce can be compared and analysed under a range of scenarios: in particular, when there is much greater propensity for healthcare seeking.Methods: A model representation of the healthcare workforce, one that formalises how the time of the different cadres is drawn into the provision of units of healthcare, was integrated with an individual-based epidemiological model - the Thanzi La Onse Model - that represents mechanistically the development of disease and ill-health and patients’ healthcare seeking behaviour. The model was applied in Malawi using routinely available data and the estimates of the volume of health servicedelivered were tested against officially recorded data. Model estimates of the “time needed” and “time available” for each cadre were compared under different assumptions for whether vacant (or established) posts are filled and healthcare seeking behaviour.Results: The model estimates of volume of each type of service delivered were in good agreement with the available data. The “time needed” for the healthcare workforce greatly exceeded the “time available” (overall by 1.82-fold), especially for pharmacists (6.37-fold) and clinicians (2.83-fold). This discrepancy would be largely mitigated if all vacant posts were filled, but the l